Impacto del programa pensión 65 en el bienestar del adulto mayor de la ciudad de Tarapoto, periodo 2012- 2014 - Leveau Tuanama, Enrique (2015)
This research entitled 65 IMPACT OF PENSION PROGRAM IN WELFARE OF ELDERLY Tarapoto, 2012-2014, aimed to determine the impact of the program on the board 65 elderly welfare of the city of Tarapoto, period 2012-2014. We worked with a type of non-experimental research, qualitative level - descriptive and longitudinal design trend; sample also consisted of one hundred seventy eight (178) pension beneficiaries 65 program in the district of Tarapoto; The data collection technique was a survey and document analysis, which had as instruments a questionnaire and a guide to data analysis, they were also used to gather the information necessary for the investigation. He finally concluded that the board 65 in the 2012 program is an adequate effect on the welfare of the adult. Also in 2014 a coverage rate of 62.36%, thereby indicating a role in the welfare of the elderly in the city of Tarapoto effect he had. It supported by the results of the statistical test Chi - square, where significance level obtained is 0.039, in which at the hypothesis, Chi estimate (13.33) value is greater than the Chi Tabular (12.59), why is accept the alternative hypothesis, stating that there is a positive effect of the pension program 65 elderly welfare of the city of Tarapoto, period 2012-2014.